Seroprevalence of contagious bovine pleuropneumonia in Ethiopian highlands (West Wellega zone, Bodji District) - Bonnet, P.; Lesnoff, Matthieu; Thiaucourt, Francois; Workalemahu, A.; Kifle, D. (2005)
Contagious bovine pleuropneumonia (CBPP) is a respiratory disease of cattle caused by Mycoplasma mycoides subsmycoides small colony. CBPP has been and is still a major cause for concern for African countries (due to mortality, animal-production losses and cost of monitoring and control). A cross sectional study of the herd and animal seroprevalence of contagious bovine pleuropneumonia (CBPP) using stratified sampling; competitive cELISA test was carried out in a zebu cattle-producing district of Ethiopia, representative of the Ethiopian highlands fringe where CBPP is assumed to re-emerge after the phasing out in 1994 of Rinderpest and CBPP bivalent vaccination program. A total of 2508 zebu cattle (Horro breed) from 300 herds were examined serologically and for characteristic clinical signs of CBPThe herd seroprevalence was 4.6% in average representing 15 herds. The herd seroprevalence was ranging from 2.0% to 8.5% in 3 strata representing increasing herd size. In conclusion, the clinical signs observed in the survey were not providing a good picture on the disease prevalence.